West European Public Perceptions of NATO and Mutual Defense Issues. - United States. International Communication Agency. Office of Research.; Crossley, Helen M. (Tufts University. Tisch Library., 2019)
This paper summarizes in text and charts some recent evidence on West European public opinion toward NATO, SALT II and related security issues. Most of the data stem from mid-1979 USIA surveys and were reported previously in oral presentations and internal memoranda.; Research Report R-27-79